Synthesis and activity of tyrosinase in mouse skin melanocytes - Nkabinde, Nkosana Cyril (Division of Cell Biology, 2018)
Tyrosinase (E.C. 1.14.18.1) is a key enzyme in the biosynthesis of melanin. The control of melanin sythesis was explored in skin melanocytes of the following strains; wild type (C57BL/6J-C/C) (which maximally synthesize melanin at normal mammalian body temperature, Himalayan (C57BL/6J-cʰ/cʰ) (which maximally synthesize melanin at temperatures below 37°C) and albino (Balb c-c/c) (a mutant which does not synthesize melanin) The effect of a-MSH on tyrosinase activity was initially investigated. A skin culture tyrosinase assay that made it possible to measure the effect of α-MSH on the activity of this enzyme in vitro was first developed. It was found that α-MSH activated the wild type and Himalayan tyrosinase in a dose-dependent manner and that this activation did not require the de novo synthesis of new enzyme. The role of glycosylation on the wild type and particularly the Himalayan tyrosinase activity was next investigated. The results do not support, but are not in conflict with the theory that the Himalayan tyrosinase is inherently underglycosylated. Translation and transcription as additional control mechanisms of tyrosinase activity was finally investigated. The correlation between the levels of tyrosinase activity, abundance of the enzyme and the synthesis of tyrosinase mRNA in wild type, Himalayan and albino mice was determined. It was shown that the levels of newly synthesized tyrosinase and tyrosinase mRNA transcripts were higher in the wild type than in the Himalayan skin. This could account for the reduced tyrosinase activity in the Himalayan mutant at normal body temperature. Low levels of tyrosinase mRNA were found in the albino skin though there was no immunodetectable enzyme in this tissue.